Proceedings of the International Seminar on Safety and Security of Autonomous Vessels (ISSAV) and European STAMP Workshop and Conference (ESWC) 2019 - Alejandro Valdez Banda, Osiris; Kujala, Pentti; Hirdaris, Spyros; Basnet, Sunil (De Gruyter, 2020)
Aalto University hosted the 2nd edition of the International Seminar on Safety and Security of Autonomous Vessels (ISSAV) together with the 7th edition of the　European STAMP Workshop and Conference (ESWC). ISSAV promotes all aspects of maritime safety and security in the context of autonomous vessels. The seminar focuses on exchanging knowledge about key safety and security challenges and opportunities in the context of autonomous vessels and the autonomous maritime ecosystem. The ESWC focuses on applications and studies related to the Systems-Theoretic Accident Model and Processes (STAMP) which is a relatively new systems-thinking approach to engineering safer systems. The 2nd edition of the International Seminar on Safety and Security of Autonomous Vessels (ISSAV) and the 7th edition of the European STAMP Workshop and Conference (ESWC) took place 17-20 September 2019 in Helsinki, Finland. Scope - ISSAV Autonomous vessels have become a topic of high interest for the maritime transport industry. Recent progress in the development of technologies enabling autonomous systems has fostered the idea that autonomous vessels will soon be a reality. However, before the first autonomous vessel can be released into her actual context of operation, it is necessary to ensure that it is safe and secure.　The aim of ISSAV is to promote all aspects of maritime safety and security in the context of autonomous vessels. The seminar focuses on exchanging knowledge about key safety and security challenges and opportunities in the context of autonomous vessels and the autonomous maritime ecosystem. The seminar has a special emphasis on: The challenges in managing safety and security in the operation of autonomous vessels and the entire ecosystem of an autonomous maritime system Innovative approaches for managing the safety of autonomous vessels, supporting the design, operations and managerial strategies for ensuring the safety in the functioning of the autonomous maritime system. Digitalization as technological enabler for efficient safety and security assurance in the context of autonomous shipping Discussion and research on how to standardize safety approaches for autonomous vessels. The development of intelligent security strategies for establishing resilient and robust systems for autonomous vessels Safety and security integration in the operative context of autonomous maritime systems Safety aspects of autonomous shipping in extreme environments　 Scope - ESWC Traditional system safety approaches are being challenged by the introduction of new technology and the increasing complexity of the systems we design, manufacture and operate. STAMP and its associated tools deal with the complexity of systems and provide systematic ways to analyze and assess existing and conceptual systems proactively or detect and illustrate deficiencies revealed through investigations. ESWC brings together researchers and practitioners who apply, or want to get familiar with, STAMP that is widely used in different sectors such as space, aviation, healthcare, defense, nuclear, railways, infrastructure and automotive. The conference covers the following topics: Experiences using STPA, STPA-Sec, and CAST Introducing STAMP, STPA, and CAST into large organizations Safety-guided and Security-guided design using STPA and STPA-Sec Using STPA to make decisions Accident/loss analyses